Pertumbuhan Jaringan Stipe dari Jamur Sagu (Volvariella sp) Endemik Papua dalam Kultur in vitro - Abbas, Barahima; Listyorini, Florentina Heningtyas; Martanto, Eko Agus; Renwarin, Yanuarius (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Sago mushrooms are edible fungus which it grew naturally on decaying sago pith. The objectives of the research were defined an appropriate formulation medium for growth and development of stipe tissue of sago mushroom in order to result spawn stages. The parent of the tissues used as explants were selected from the best performance of sago mushroom which grew naturally. The research divided into three experiments: 1) Initiation of growth hyphae from stipe tissue; 2) hyphae proliferation; and 3) spawn formation. Murashige and Skoog (MS) and Knudson-C (KN) medium enriched 15 and 30% coconut water are the best medium for growth initiation and proliferation of hyphae. Both of these medium induced the explant grew rapidly and resulted vigorous hyphae. No different effect among concentration treatment of coconut water was observed for initiation and proliferation hyphae. The fact that all of the formulation medium used for spawn formation were able to induce spawn development become spawn stage. Even so, the best mediums for spawn formation were medium formulation 9 and 10.